Development of PUHA (Pop Up Horses Algebra) educational games for enhancing grade 7 students' algebraic learning - Agus Miftakus Surur; Zulfa Mufidatul Inayah; Putri Farica; Budi Cahyono; Khoivatus Suhana; Hasnah Binti Mohamed (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The PUHA (Pop Up Horses Algebra) game is developed for enhancing mathematics learning in Grade 7 algebra. This research aims to create interactive games that are not only engaging but also effective in facilitating students' comprehension of algebraic concepts in an enjoyable manner. Employing the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) as a developmental framework, this study endeavors to ensure the systematic and structured creation of PUHA. The findings underscore that the development of PUHA games significantly enhances students' grasp of algebraic principles at the Grade 7 level. Utilizing the ADDIE Model for PUHA game development ensures a methodical approach, guaranteeing the production of high-quality and impactful educational games. In conclusion, the development of the PUHA game utilizing the ADDIE Model showcases a promising approach to fostering students' algebraic understanding in Grade 7 through engaging and effective educational gaming experiences.